Desperate Times Call for Desperate Measures: Use of Continuous Subcutaneous 1-34 PTH Infusion for Postsurgical Hypoparathyroidism - Haider, Adnan (Case Rep Endocrinol, 2021)
OBJECTIVE: This case highlights use of 1-34 PTH continuous infusion in a patient with postsurgical hypoparathyroidism. METHOD: Clinical presentation and biochemical profile were monitored before and after 1-34 PTH infusion, with notable reduction in pill burden in a patient with postsurgical hypoparathyroidism. RESULTS: We present a case of postsurgical hypoparathyroidism following thyroidectomy for Graves disease. The patient was requiring a total of 34 pills daily and, despite medication compliance, her clinical and biochemical control was unsatisfactory. Following initiation of 1-34 PTH in the form of a subcutaneous pump, we were able to stop all calcium supplementation and reduce calcitriol to 0.5 mcg daily. Her current biochemical control as well as quality of life improved significantly on CSPI, calcitriol, and a daily serving of dietary calcium. CONCLUSION: This case highlights the use of 1-34 PTH either as twice-daily dosing or continuous subcutaneous infusion for adult patients with hypoparathyroidism.